BOARD ATTRIBUTES AND TAX AGGRESSIVENESS OF LISTED MANUFACTURING FIRMS IN NIGERIA - Oluwasegun Temitayo Odunsi; Abdul-Azeez Adeniyi Alao; Opeoluwa Paul Fakayode (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
The pursuit of wealth maximization by shareholders and the government's goal of maximizing tax revenue are often at odds, with an aggressive tax system at the heart of this conflict. Despite corporate growth, the tax contributions from manufacturing firms have been decreasing, causing concern for the government. This study therefore investigated the effect of board attributes on tax aggressiveness among listed manufacturing firms in Nigeria. Specifically, this study examined the effect of board size on tax aggressiveness among listed manufacturing firms in Nigeria. Ex-post facto design was employed in the study with secondary data being gathered from published annual reports of these companies from 2012 up to 2021. The finding conforms with the results of Olaniyi & Okerekeoti (2022) and Kalbuana et al., (2023). This shows that big-sized companies among manufacturing companies quoted in Nigeria tend to be more tax aggressive. The study concluded that board size significantly affects tax aggressiveness in these companies. Consequently, it suggested that the Federal Inland Revenue Service (FIRS) need to promote transparency in tax reporting by encouraging companies to disclose their tax planning strategies, particularly given the significant influence of larger boards of directors on tax behaviour. This can be achieved by establishing detailed tax reporting standards that explicitly define acceptable and unacceptable tax practices, particularly concerning tax planning. Also, FIRS should promote board education on tax-related matters by organizing workshops and regular training sessions tailored to board members, focusing on the latest tax policies, compliance obligations, and tax planning strategies.